THE WAYS OF GIVING APPROPRIATE INSTRUCTIONS - Auelbekova, Balxadisha Serik qizi; Burkhanova, Mamura Gulyamovna (Innovative Development in Educational Activities, 2022)
The significance of providing clear directions in the second-language classroom will be explored in this article along with the justification for doing so methods for communicating instructions clearly.